Republic of Congo : Staff Report for the 2003 Article IV Consultation and a New Staff-Monitored Program. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2003)
This paper examines the Republic of Congo's 2003 Article IV Consultation and a New Staff-Monitored Program (SMP). Performance under IMF-supported programs and recent SMPs was disappointing. Major progress has been made in consolidating security and peace, and in establishing democratic institutions. The public finances deteriorated in 2002, reflecting a combination of expenditure overruns and a drop in non-oil revenue collection. The drop in non-oil revenue was more pronounced at customs, owing to large-scale fraud and widespread use of ad hoc exemptions. As a result, most targets under the 2002 SMP were missed.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet